Pengembangan Instrumen Pengukuran Gaya Belajar Konsumen - Murwani, F. Danardana (Jurnal Aplikasi Manajemen, 2009)
This research was intended to develop and validate the measurement instrument of consumer's learning style in supermarket context. The theoretical framework of this study was based on the convergence of student's learning style models and consumer's buying decision model. Confirmatory factor analysis successfully validated the unidimensionality, composite reliability, and construct validity of the measurement instrument.